A study on the abandonment of housing projects in the state of Kedah, Malaysia - Mohit, Mohammad Abdul; Nursobah, Siti (2005)
Housing projects remaining incomplete or abandoned at a later time have been almost regular phenomena in recent decades in Malaysia. According to the Ministry of Housing and Local Government of Malaysia, by the end of 2004, a total of 227 housing projects were abandoned, involving 75,356 units and 50,813 house buyers and the total value stands at RM7.03 or US$1.9 billions. Nevertheless, so far no systematic study has been done to analyse the situation, identify the reasons and impacts on different parties. Therefore, this paper is focused to identify the reasons and study the different impacts of the abandonment of housing projects in the state of Kedah, Malaysia, where a total of 22 projects were declared abandoned during 1987-1996, involving 4,056 units of houses worth of RM313.8 or US$83.7 million.